2003
DOI: 10.1007/s00701-003-0150-y
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic acute subdural haematomas of the posterior fossa: clinicoradiological analysis of 24 patients

Abstract: acute posterior fossa subdural haematomas can be divided into two distinct groups: those patients admitted in a comatose state and those with a moderate/mild head injury on admission. Comatose patients present usually with signs of posterior fossa mass effect and have a high percentage of bad outcomes. On the contrary, patients admitted with a GCS of 8 or higher are expected to recover. In these patients the thickness of the haematoma (<1 cm) seems to be a guide to indicate surgical evacuation of the haematoma. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
1
20
0
5
Order By: Relevance
“…11 The commonest age group affected by the intracranial lesions was > 20-30 years and the least age group affected by those injuries was > 70 years. These results were in agreement with a study done by Ommaya, 12 while there was disagreement with a study in Japan that stated that the commonest age group affected by the intracranial lesions was > 40-60 years and the least age group was < 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…11 The commonest age group affected by the intracranial lesions was > 20-30 years and the least age group affected by those injuries was > 70 years. These results were in agreement with a study done by Ommaya, 12 while there was disagreement with a study in Japan that stated that the commonest age group affected by the intracranial lesions was > 40-60 years and the least age group was < 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…This study included 18 prognostic models reported in 13 studies ( Figure 1) [4,5,[9][10][11][12][13][14][15][16][17][18][19]. Often reported predictors were age, clinical conditions on admission, head CT features and cerebral haemodynamic monitoring (Table I).…”
Section: Resultsmentioning
confidence: 98%
“…24%) according to the model reported by Klauber et al [4], while the probability of unfavourable outcome was 100/ {1 þ exp[À (2.9497 Ã 2 À 1.1384)]} (i.e. 99.2%) according to the model by d'Avella et al [5]. For a specific patient, different models will probably offer various, even contradictory p.…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical manifestations of SIEDH are headache, vomiting, neck resistance, and lack of the typical signs of nervous system orientation. The condition may rapidly deteriorate, causing compression of the transverse sinus and brain stem and subsequently death of the patient (1)(2)(3)(4)(5)(6)(7)(8)(9). This type of epidural hematoma mainly occurs due to occipital deceleration injury, most often associated with occipital bone fracture or lambdoid suture separation (3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…Although SIEDH is associated with typical characteristics, it might be difficult to diagnose when presenting as infratentorial acute epidural hematoma, which is clinically silent and has nonspecific symptoms (2). However, this type of hematoma can often be rapidly deteriorating, causing a sharp rise in intracranial pressure that leads to a lifethreatening foramen magnum herniation.…”
Section: Introductionmentioning
confidence: 99%